The Analysis of Green Supply Chain to Improve Performance Solid Product Using SCOR Analysis at Pharmaceutical Company, Jakarta - Raga, Panji Dewa Jayeng; Sutawijaya, Ahmad H.; Nawangsari, Lenny C. (International Review of Management and Marketing, 2021)
In improving the performance of pharmaceutical companies, it is necessary to implement a green supply chain using the Supply Chain Operation References (SCOR) method. Several pharmaceutical KPI deviations during 2016-2018 such as Supplier Irregularities, Documentation Errors, CO2 Energy complaints, Water-H2O complaints, and Waste. Therefore, green manufacturing is a production process that uses inputs with relatively low environmental impact, is efficient, and produces little waste or pollution. This study aims to analyze the performance of the Green Supply Chain in pharmaceutical companies in Jakarta by using Supply Chain Operation References (SCOR). This study uses quantitative methods and qualitative methods with a focus on measuring the performance of green manufacturing. The population and samples in this study were all sales and operating planning divisions, supply chain divisions, logistic divisions, commercial divisions, production divisions, procurement divisions, engineering and health divisions and environmental safety divisions. The results of research using green SCOR show that the performance value of green pharmaceutical manufacturing is 96.506 (very good) and is a new way of monitoring the performance of pharmaceutical companies Keywords: Supply Chain, Green Supply Chain, Supply Chain Operation References (SCOR) JEL Classifications: L2, J2 DOI: https://doi.org/10.32479/irmm.10777